(untitled) (Journal of Economic Research & Business Administration, 2016)
In the modern, quickly changing situation the management of the enterprise for adoption of reasonable administrative decisions needs to carry out constantly the analysis of activity of the enterprise for what the initial information received from a number of indicators one of which is prime cost is necessary. The accounting of the expenses caused by process of the organization of service of production and management is important in the domestic organizations and in the foreign companies as, finally, overhead costs have to be surely included in full product cost. Information grouped in objects of the accounting of expenses has to meet the requirements of management and form the basis for a partition of expenses between a work in progress and finished goods and for calculation of both all release, and separate products.